Asymmetric Donor–Acceptor 2,7-Disubstituted Fluorenes and Their 9-Diazoderivatives: Synthesis, Optical Spectra and Photolysis - Andrei I. Savchenko; Vladimir N. Belov; Mariano L. Bossi; Stefan W. Hell (Molecules)
In a search for dyes photoactivatable with visible light, fluorenes with substituents at positions 2 and 7 were prepared, and their absorption and emission spectra were studied. In particular, the synthesis route to 9-diazofluorenes with 2-(N,N-dialkylamino) and N-modified 7-(4-pyridyl) substituents was established. These compounds are initially non-fluorescent, undergo photolysis with UV or blue light, and—in non-polar media—provide orange- to red-emitting products with a large separation between absorption and emission bands. Irradiation of non-fluorescent 9-diazoderivative 20 in dioxane with the light of 365 nm or 470 nm was accompanied by strong fluorescence gain (10 to 20 times), orange–red emission, and a large Stokes shift of photoproducts, which structurally relate to fluorescent betaine 13 (model compound without diazo group). Photolysis of 20 in protic solvents (ROH = MeOH, H2O) provided clean transformation to C9-OR derivatives, though the emission gain in protic solvents was low.